POWER DISTANCE AND VALUE ORIENTATIONS INFLUENCE ON OLIGARCHISM AND CRONY-SECTORS DEVELOPMENT IN MODERN ECOMNOMIC SYSTEMS - V. Kozyuk; O. Dluhopolskyi (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The relationship between oligarchic economies and crony-sectors development, which includes industries with domination of rent-seeking behavior, is made. The relationship between power distance and some indicators of socio-economic development, value orientations of economic systems is analyzed. The correlation-regression analysis of power distance and crony capitalism dependence has been carried out. The existence of "bad locked circle", associated with tolerance of hierarchies, is debated. The conclusions about fact that cultural factors of hierarchical society's formation have direct effect on the spread in the economic system crony sectors and weak institutions are made.